The role of female teachers in enhancing the intellectual security of high school students in Madaba schools in Jordan from the point of view of the female teachers - Abu Aysheh, Sana'a Abedrabbo (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to reveal the role of female teachers in the intellectual security of high school students in Madaba Governorate schools. The objectives of the study were the researcher followed the descriptive analytical approach and applied an electronic questionnaire after placing its validity and reliability on a random sample of (55) female teachers from a community of (296) female High schools teachers in Madaba. The results showed: that the role of female teachers in the intellectual security project among high school students in Madaba governorate schools was (α≤0.05) statistically (a = 0.05) due to the effect of school type, and there were no statistically significant differences (α≤0.05) due to the effect of educational qualification. In light of the results, the researcher recommended several recommendations, the most important of which are: the need for female teachers to play their leading role in pushing the dangers of extremist ideas since their inception, and the need to prepare programs, seminars and awareness lectures for the community, family and students, and to increase the effectiveness of the role of female teachers in developing intellectual security among school students.
Keywords: the role of female teachers; promotion; intellectual security